Islamic banks credit risk performance for home financing: Before and during Covid-19 pandemic - MB Hendrie Anto; Faaza Fakhrunnas; Yunice Karina Tumewang (Economic Journal of Emerging Markets, 2022)
Purpose ― This study aims to assess the home financing credit risk performed by Islamic banks in Indonesia. Methods ― A panel dynamic analysis is adopted to measure the bad loan performance before and during the Covid-19 pandemic. The observation period started from January 2016 to September 2020 with 1,881 observation periods of monthly panel data from the province level. Findings ― The study finds a difference in bad loan performance before and during the Covid-19 pandemic. Before this pandemic, inflation has a positive and significant influence on non-performing financing in real estate, rental business, and company service. However, during the Covid-19 pandemic, a substantial and positive effect of inflation is found on the bad loan for personal flat and apartment ownership. On the other hand, a significant and negative impact of inflation is found on the bad home loan for personal business shop ownership. Implication ― This analysis could trigger the government to provide financial assistance for those affected by the Covid-19 crisis. In addition to that, an Islamic bank is also expected to give financing allowances for them by providing an option of debt restructuration and rescheduling. Originality ― This paper analyses the Islamic bank’s credit risk performance for home financing before and during the Covid-19 pandemic. This issue has not been presented in the literature to the best of our knowledge.